Numerical Analysis of Load-Bearing Capacity in Contaminated and Uncontaminated Soils Treated with Nanomaterials - Abd Hacheem, Zuhair; Al-Khyat, Sahar; Saleh, May Samir; Hasan, Hayder A. (Salehan Institute of Higher Education, 2025)
Construction of load-bearing structures requires both a strong foundation and stable soil. For projects located on weak or contaminated soils, stabilization techniques are a prerequisite. Nanotechnology holds promise for improving soil strength and stability, offering innovative solutions for enhancing site conditions in geotechnical engineering. This numerical study explores the potential application of nano-clay (NC) and nano-silica (NS) in improving the overall load-bearing performance of a strip footing resting on clean and kerosene-contaminated soils. The objectives are to assess the impact of varying nanoparticle contents and curing durations on soil performance. Results suggested that adding NC and NS substantially enhances the bearing capacity ratio (BCR) up to a maximum of 4.76 and 4.33 at 1% NC and 1.5% NS, respectively, compared to untreated soil. Overdosing, however, resulted in reduced effectiveness, emphasizing the significance of optimal contents. Conversely, the BCR improvement was less noticeable in kerosene-contaminated soils until it peaked at 2.5% NS and 2% NC. However, results of both clean and contaminated soils revealed that nanomaterials negatively impact settlement behavior. Curing age was found to be a major factor affecting BCR, in which treated soils showed a consistent increase in BCR over time. These findings endorse the potential of nanomaterials for stabilizing soil used in geotechnical engineering. Careful selection of dosages and consideration of soil contamination are critical to optimizing performance in complex geotechnical conditions.